WEB-BASED OF STUDENT ENTREPRENEURSHIP PROJECT MANAGEMENT APPLICATION - Nuraeni Dahri; mallisza, Danyl Mallisza; Fenjeli Sonata Laoli (Ikatan Dosen Menulis, 2025)
Entrepreneurship project management in the Diploma III Information Management Study Program at Ekasakti University is still conventional and manual. The use of social media applications and Google Drive in entrepreneurship project management has not been able to support manual project management. The lack of an integrated system complicates the project management process and is inefficient for students. A web-based entrepreneurial project management system was designed to simplify the process of proposal submission, logbook filling, reporting, and assessment. The design method used a waterfall approach. The design tool used was Unified Modeling Language (UML) to visualize user requirements and workflows. The design results in a website with integrated features such as project submission, logbook upload, lecturer evaluation, and digital report storage.